Sustainability Dimensions Assessment in Four Traditional Agricultural Systems in the Amazon - Heredia-R, Marco; Torres, Bolier; Vasseur, Liette; Puhl, Laura; Barreto, Deniz; Díaz-Ambrona, Carlos G. H. (Frontiers in Sustainable Food Systems, 2022)
Although traditional agriculture carried out by ethnic groups is considered biodiversity-friendly and important for food security and sovereignty, few studies have investigated the potential of these systems in the interest of promoting a sustainable agricultural development policy according to United Nations Sustainable Development Goals. Using the FAO's Sustainability Assessment of Food and Agriculture (SAFA) methodology, this study analyzed the sustainability of four traditional agricultural systems, three indigenous (Waorani, Shuar, and Kichwa) and one migrant settler populations in the Yasuní Biosphere Reserve (YBR) and identified synergies and trade-offs among the dimensions of sustainability. The results showed different dynamics in all dimensions of sustainability-specifically, trade-offs in the dimensions of good governance with environmental integrity and social well-being, economic resilience, and social well-being. It was identified that the differences in terms of sustainability are narrowing between the indigenous Shuar people’s traditional agricultural systems and those of migrant settlers, which provides policymakers with specific information to design sustainable development policies and rescue traditional agricultural systems in the Amazon region.